Avaliação silvicultural e produtiva da Jatropha curcas (Linnaeus) no município de Cássia, MG - Pires, Thiago Pinto; Silva, Magali Ribeiro da [UNESP]; Netto, Sylvio Péllico (My University, 2010)
The species Jatropha curcas (Linnaeus) belongs to the family Euphorbiaceae, popularly known as pinhão-manso, with many attributes, multiple uses and considerable potential for biodiesel production. This work was conducted with the pinhão-manso, in the Reata Farm, MG, in four experiments to evaluate the time of collecting seeds, its germination, the growth of seedlings in nursery, and tree structure in adulthood. Statistical analysis was conducted with experimental implementation of ANOVA and Tukey test to detect differences between means. It was concluded that the seeds attacked by bedbug Pachycoris torridus, taken in March and April, germination percentages were much lower than those that had not been attacked by this insect, harvested in January. The treatment that had reached the best result (PG = 60% and VfG = 2.64 s/day) was the T1S3, whose seeds were collected in January and with substrate land + 20% + NPK dung; and the treatment that hit the lower germination percentage was T3S2 (PG = 21.25%), whose seeds were collected in April and substrate land + 25% M.O. Seeds harvested in March, regardless of substrate used, were those that reached the lowest rate of fi nal germination speed. The tests showed the need for a pest control for conducting sprocket nut plantations with purposes of seed production in areas where there is the presence of P. torridus. The best substrate for development from was the 3 (composed of ground beef manure + 20% + NPK - 0.3 kg m- ³ super simple, 0.05% potassium chloride). The experiment showed that the seeds collected in March and April after the attack of the bedbug P. torridus, besides their germination percentages were much lower than those which had not undergone the attack, also gave rise to individuals with lower growth rates. The plant of pinhão-manso in its broadleaf period did not have signifi cant differences in latex exudation throughout the day as there was no correlation between height and the number of branches; this means that the amount of branches that an individual has is one factor that can be genetically selected, in order to increase future production of seed per individual.

A espécie Jatropha curcas (Linnaeus) pertence à família Euphorbiaceae, conhecida popularmente como pinhão-manso, com muitos atributos, múltiplos usos e um considerável potencial para a fabricação de biodiesel. O presente trabalho foi conduzido com o pinhão-manso, na Fazenda Reata, MG, em quatro experimentos, com o objetivo de avaliar a época da coleta das sementes, sua germinação, crescimento das mudas em viveiro e estrutura arbórea das árvores na fase adulta. A análise estatística experimental foi conduzida com aplicação de análise de variância e teste de Tukey para detecção de diferenças entre médias. Concluiu-se que as sementes atacadas pelo percevejo Pachycoris torridus, colhidas em março e abril, atingiram percentagens de germinação muito inferiores àquelas que não sofreram o ataque desse inseto, colhidas em janeiro. O tratamento que atingiu o melhor resultado (PG = 60% e VfG = 2,64 s/dia) foi o T1S3, cujas sementes foram colhidas em janeiro e com substrato terra + 20% esterco + NPK; e o tratamento que atingiu a menor percentagem de germinação foi T3S2 (PG=21,25%), cujas sementes foram colhidas em abril e com substrato terra + 25% M.O. As sementes colhidas em março, independente do substrato utilizado, foram as que atingiram menores taxas de velocidade fi nal de germinação. Os ensaios mostram a necessidade de um controle de pragas para a condução de plantios de pinhão-manso com fi ns de produção de sementes em áreas onde há a presença do P. torridus. O melhor substrato para o desenvolvimento do pinhão-manso foi o 3 (composto de terra + 20% esterco bovino + NPK - 0,3 kg m- ³ de super simples, 0,05% de cloreto de potássio). O experimento comprovou que as sementes coletadas em março e abril, após o ataque do percevejo P. torridus, além de apresentarem percentagens de germinação muito inferiores àquelas que não sofreram o ataque, deram origem também a indivíduos com menores taxas de crescimento. A planta de pinhão-manso no período caducifólio não apresenta diferença signi- fi cativa na exudação de látex ao longo do dia. Como não houve correlação entre altura e o número de ramifi cações, isto signifi ca que a quantidade de ramos que um indivíduo possui é um fator que pode ser selecionado geneticamente, com o fi to de se aumentar futuramente a produção de sementes por indivíduo.
Silvicultural and productive evaluation of Jatropha curcas (Linnaeus) in the municipality of Cássia, MG
Keywords: Pinhão-manso; Biodiesel; Germination; Substrate; Pinhão-manso; Biodiesel; Germinação; Substrato